Depressive reactions as an outcome of stress processes: The study on imprisonment - Buško, Vesna (Array, 2001)
Based on hypotheses of the transactional stress and coping theory, the study examines the role of individual, situational and mediating cognitive factors in accounting for depression in prison inmates. Relevant demographic and criminological measures, and self-report instruments for the assessment of several personality dimensions, situational features, and mediating processes - cognitive appraisals and coping strategies, were taken in the sample of 475 males imprisoned in Croatian penal institutions. Zung Self-report Depression Scale was administered as a short-term measure of inmate adjustment to imprisonment. Hierarchical regression procedures were performed to assess relative predictive power of particular groups of individual, situational and mediating variables, with the cognitive appraisal on event controllability taken as a moderator variable. Results showed that personality dimensions and two sets of mediating processes variables significantly contributed to the criterion variance, with both levels of perceived controllability. Total amount of variance in depression scores explained by the whole system of employed predictors was 41% and 54%, for the low and high event controllability groups, respectively. Observed moderator effects of event controllability primarily refer to the role of coping strategies, i.e., to the amount of their additive contribution, and dissimilar adaptive value of particular strategies in situations differing in the level of perceived controllability.